(untitled) (Research, Society and Development, 2020)
Objective: To identify the characteristics and evidence of studies on neuroethics and neuroeducation in the scientific literature. Method: Integrative review held in the SCOPUS, PUBMED and Web of Science databases. From the analysis of 613 papers, we selected 25 for analysis according to established criteria. Results: From the analysis of the evidence, its results were presented in three main groups: 1) Increased performance and perception through training; 2) Increased performance through medicalization and interventions; and 3) Discussion and criticism on neuroethics and neuroeducation. Conclusion: Both neuroeducation and neuroethics have the potential to benefit society, in future theoretical and technological developments on health and education. Their repercussions and translations achieve the professional field of Nursing, which requires a critical appropriation of their foundations, in such a way as to preserve general principles of their application, such as justice and equity in the enjoyment of their benefits, control of interests and respect for cultural and moral plurality and individuality.